2017
DOI: 10.1038/s41598-017-03729-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Nanoparticles on Skin Allergy

Abstract: In recent years there has been considerable effort to understand the interaction of nanomaterials with the skin. In this study we use an in vivo mouse model of allergic contact dermatitis to investigate how nanoparticles (NPs) may alter allergic responses in skin. We investigate a variety of NPs that vary in size, charge and composition. Results show that small (<200 nm) negative and neutral charged NPs exhibit an immunosuppressive effect but that positively charged NPs do not. Confocal imaging suggests positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 42 publications
12
48
1
Order By: Relevance
“…The in vitro data is suggestive of potential MWCNT induced dermal irritation, and to examine the effect of these MWCNTs on normal and inflamed skin, our lab uses hairless C57BL/6 mice treated with either vehicle or a DNFB sensitizer. As we have previously reported, topically applied MWCNT High-COOH particles exacerbate the DNFB induced CHS ear swelling response 24 h after co-challenge with 0.2% DNFB and 1 μg/ear MWCNT High-COOH [34]. This response appears to be synergistic as the MWCNT High-COOH particles have no effect on ear swelling without the sensitizer (Fig.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The in vitro data is suggestive of potential MWCNT induced dermal irritation, and to examine the effect of these MWCNTs on normal and inflamed skin, our lab uses hairless C57BL/6 mice treated with either vehicle or a DNFB sensitizer. As we have previously reported, topically applied MWCNT High-COOH particles exacerbate the DNFB induced CHS ear swelling response 24 h after co-challenge with 0.2% DNFB and 1 μg/ear MWCNT High-COOH [34]. This response appears to be synergistic as the MWCNT High-COOH particles have no effect on ear swelling without the sensitizer (Fig.…”
Section: Resultssupporting
confidence: 57%
“…We previously reported that the exacerbation of CHS induced ear swelling caused by the MWCNT High-COOH was associated with increased mast cell degranulation [34]. Here we examined the levels of both mast cell and basophil degranulation by counting the number of degranulating and intact cells in toluidine blue stained skin sections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the size, the surface charge, chemical composition, shape and solubility makes them attractive for AIT. Jatana et al determined the influence of size and charge of different nanoparticles (gold, silver, silica, and titanium dioxide) on immunomodulation in a mouse model of allergic contact dermatitis and concluded that small and negatively charged nanoparticles exhibited immunosuppressive effects [82]. Biodegradable polymeric nanoparticles that are biocompatible with tissues and cells, can be promising candidates in AIT that might reduce the unwanted side effects associated with the current therapy, using alum as adjuvant.…”
Section: Physicochemical Properties Of Nanoparticlesmentioning
confidence: 99%